2018
DOI: 10.4149/neo_2018_170918n595
|View full text |Cite
|
Sign up to set email alerts
|

MACC1 silencing inhibits cell proliferation and induces cell apoptosis of lung adenocarcinoma cells through the β-catenin pathway

Abstract: It has been documented that over-expression of metastasis-associated in colon cancer-1 (MACC1) is related to poor prognosis in non-small cell lung cancer (NSCLC). This study investigates the function and underlying molecular mechanisms of MACC1 in lung adenocarcinoma. Here, we firstly employed immunohistochemistry, western blotting, real-time PCR, and online database to demonstrate that MACC1 expression was elevated in tumor tissues compared with tumoradjacent or normal tissues. Real-time PCR, CCK-8, colony fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 33 publications
1
9
0
Order By: Relevance
“…Scholars reported MACC acted as an oncogene involved in cancer progress and metastasis and predicted a poor prognosis in many cancers (17)(18)(19)(20)(21)(22)(23)(24)(25). Moreover, many scholars revealed that MACC1 expression has also been associated with treatment response via interrupting Notch pathway (26), b-catenin (27,28), and HGF/cMet pathway (29). These investigations implicate MACC1 as a multifunctional regulator of cancer progression.…”
Section: Introductionmentioning
confidence: 99%
“…Scholars reported MACC acted as an oncogene involved in cancer progress and metastasis and predicted a poor prognosis in many cancers (17)(18)(19)(20)(21)(22)(23)(24)(25). Moreover, many scholars revealed that MACC1 expression has also been associated with treatment response via interrupting Notch pathway (26), b-catenin (27,28), and HGF/cMet pathway (29). These investigations implicate MACC1 as a multifunctional regulator of cancer progression.…”
Section: Introductionmentioning
confidence: 99%
“…For example, MACC1 improves the cisplatin resistance partially in lung cancer via the PI3K/AKT pathway, 51 whereas its depletion suppresses lung cancer cell proliferation and causes cell apoptosis through the β-catenin pathway. 52 Furthermore, MACC1 is implicated in the control of HGF/Met and MEK/ERK pathways in ovarian cancer, 53 Akt/β-catenin pathway in nasopharyngeal carcinoma, 54 and HGF/c-MET/AKT pathway in hepatocellular carcinoma. 55 Our study did not explore the effects of LINC00519 on these signaling pathways that were under the control of MACC1.…”
Section: Discussionmentioning
confidence: 99%
“…Cell cycle analysis. The cell cycle distribution was detected using a propidium iodide (PI)-based cell cycle analysis kit (Beyotime Institute of Biotechnology), as previously described (20). The principle of this method is that the nuclei of dead cells can be stained by PI.…”
Section: Methodsmentioning
confidence: 99%